PENGALAMAN ORANG TUA DALAM MENGHADAPI PERILAKU SIBLING RIVALRY PADA ANAK - Lazdia, Wenny; Kusuma, Vinna Cahaya (REAL in Nursing Journal, 2019)
A child's relationship is very important is with his parents. Phenomenon Based on a preliminary survey conducted by researchers, researchers conducted interviews with both parents at TK Listrina, parents applying an authoritarian parenting style seen from how to educate children by requiring children to read so that with this parent's attitude the child feels burdened or depressed about excessive descent demands.This study aims to explore the experience of parents with Sibling Rivalry behavior. and understand parenting to overcome sibling competitive behavior in early childhood. Qualitative method with a phenomenological approach. This research was conducted at Ristina Antokan Maninjau Kindergarten. Participants in this study were 7 parents of students who experienced children with sibling competitions taken by purposive sampling. collecting data through in-depth interviews and observations and then using the colaizzi method.The results of the study: of the 3 themes of the results of this study namely parenting practices adopted by most participants, namely authoritarian parenting because parents tend to behave arbitrarily towards children and side with one child and demand that children follow their parents' orders. there are still many parents who do not know about sibling prevention in children and strategies for dealing with sibling competition. Keywords: parental experience, sibling competition, children